Specification and Verification of Multi-agent Systems - Dastani, Mehdi; Hindriks, Koen V.; Meyer, John-Jules (Springer US : Imprint: Springer, 2010)
Specification and Verification of Multi-agent Systems presents a coherent treatment of the area of formal specification and verification of agent-based systems with a special focus on verification of multi-agent programs. This edited volume includes contributions from international leading researchers in the area, addressing logical formalisms and techniques, such as model checking, theorem proving, and axiomatisations for (semi) automatic verification of agent-based systems. Chapters include: • Using Theorem Proving to Verify Properties of Agent Programs • The Refinement of Multi-Agent Systems • Model Checking Agent Communication • Directions for Agent Model Checking • Model Checking Logics of Strategic Ability: Complexity • Correctness of Mult-Agent Programs: A Hybrid Approach • The Norm Implementation Problem in Normative Multi-Agent Systems • A Verification Logic for GOAL Agents • Using the Maude Term Rewriting Language for Agent Development with Formal Foundations • The Cognitive Agents Specification Language and Verification Environment • A Temporal Trace Language for Formal Modelling and Analysis of Agent Systemns • Assurance of Agent Systems: What Role Should Formal Verification Play? Specification and Verification of Multi-agent Systems is a comprehensive guide that makes a useful tool for researchers, practitioners and students, and serves as a reference work summarizing the state of the art in an accessible manner.